2020
DOI: 10.3389/fvets.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Endotracheal Tube Cuff Pressure and the Use of Three Cuff Inflation Syringe Devices in Dogs

Abstract: Over-inflation of an endotracheal tube (ETT) cuff may lead to tracheal mucosal irritation, tracheal wall ischemia or necrosis, whereas under-inflation increases the risk of pulmonary aspiration as well as leaking anesthetic gas and polluting the environment. The objectives of this two-phase study were to (1) identify the incidence of improper ETT cuff inflation (both over-and under-inflation) using the minimum occlusive volume (MOV) technique coupled with a regular injectable syringe in the anesthetized dogs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
8
0
4
Order By: Relevance
“…This result is not in line with evidence obtained in humans [ 27 , 28 , 29 ], as well as in dogs and cats [ 1 , 2 , 30 , 31 ] establishing the inferiority of MOV to the use of a manometer in achieving a pre-specified (i.e., target) cuff pressure. Furthermore, when comparing MOV in cats and dogs to the use of commercially available syringe inflation devices, MOV proved inferior [ 2 , 32 ]. Whereas these studies clearly concluded that a cuff manometer should be used to achieve optimal ETT cuff pressure, the use of MOV was three times more common than cuff pressure measurement in dogs and cats in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not in line with evidence obtained in humans [ 27 , 28 , 29 ], as well as in dogs and cats [ 1 , 2 , 30 , 31 ] establishing the inferiority of MOV to the use of a manometer in achieving a pre-specified (i.e., target) cuff pressure. Furthermore, when comparing MOV in cats and dogs to the use of commercially available syringe inflation devices, MOV proved inferior [ 2 , 32 ]. Whereas these studies clearly concluded that a cuff manometer should be used to achieve optimal ETT cuff pressure, the use of MOV was three times more common than cuff pressure measurement in dogs and cats in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A inserção do traqueotubo de forma ríspida pode lesionar o músculo cricoaritenoideo, as articulações cricotireoideas e por consequência comprometer a função laríngea (Brown, 2007;Camargo et al, 2022). Uma hiperinsuflação do cuff pode levar a isquemia e lesão do nervo laríngeo recorrente, estudos indicam limite máximo de pressão do cuff variando entre 18 mmHg e 24 mmHg monitorados através de uma seringa medidora de pressão que é a técnica mais eficiente para controlar a pressão de insuflação e evitar lesões (Briganti et al, 2012;Castilho et al, 2003;Hung et al, 2020). No presente caso não foi utilizado um método de avaliação da pressão utilizada para insuflar o cuff, o que pode ter favorecido uma pressão excessiva e uma possível lesão nervosa através da compressão e comprometimento da microcirculação nervosa como já descrito em outros estudos (Camargo et al, 2022;Daly et al, 2022;Evman & Selcuk, 2020;Rodriguez et al, 2020).…”
Section: Discussionunclassified
“…Overinflation of an ETT cuff may also lead to tracheal ischaemia and necrosis. Therefore, the most efficient technique in controlling the inflation pressure and to avoid these lesions is by using an accurate cuff pressure control syringe 22…”
Section: Discussionmentioning
confidence: 99%